Pemanfaatan Aplikasi Sipmen Dalam Proses Pencatatan Distribusi Dokumen ST2023 di Badan Pusat Statistik Kabupaten Lombok Timur - Aulia Syifa; Annisa Syifa Zahro; Amalia Agustina; Muhammad Rijal Alfian (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The Agricultural Census 2023 (ST2023) is a large-scale activity carried out by BPS. The series of ST2023 activities consists of planning, preparation, data collection, data processing, presentation and data analysis. One of the data processing stages is inputting documents using the Document Management System (SIPMEN). The SIPMEN application is used by all work units at BPS throughout Indonesia which carry out ST2023 data collection using the Paper Assisted Personal Interviewing (PAPI) method. The purpose of using the SIPMEN application by BPS East Lombok Regency is to facilitate the management of ST2023 documents starting from the document distribution process, namely receipt from BPS NTB Province to the process of receiving documents from BPS East Lombok Regency data collection, namely batching (grouping) documents.